KUALITAS SPERMA PADA REMAJA PEROKOK DI LINGKUNGAN UNIVERSITAS UDAYANA - Rizal, Sally Nabila; Sukmaningsih, A.A.S. A.; Wirasiti, Ni Nyoman (SIMBIOSIS, 2023)
Smoking is a familiar behavior for male adolescents. The reason is because cigarette contains toxins which can increase our Reactive Oxygen Species (ROS) and causes tissue oxidative stress, thereby disrupting the quality of spermatozoa. The purpose of this study is to determine the quality of sperm on adolescent smokers in Udayana University. The samples were taken from 30 male adolescents with an age range of 18 – 24 years old. This included 15 smokers and 15 non-smokers as the control group. The macroscopic observations included color, smell, liquefaction, volume, consistency and sperm pH – while the macroscopic observations included concentration, morphology, motility, viability, and membrane integrity. This study used a comparative method. The qualitative data included the color and smell of spermatozoa, while the quantitative data included concentration, morphology, motility, liquefaction, volume, consistency, viability, membrane integrity and pH – all which were presented in the form of mean and standard deviation. The quantitative data were analyzed statisticall with t test using SPSS application. The results obtained from this study showed that liquefaction, volume, consistency, motility, viability, concentration, and morphology of spermatozoa in smokers had a decrease compared to non-smokers (p < 0.01). Meanwhile, color, smell, pH, and integrity of spermatozoa membranes showed no significant difference between smokers and non-smokers (p > 0.01).